Collaboration and Cognitive Skills in the Workplace: Results from the PIAAC Survey - Joshua Collins; Jill Zarestky; Ellen Scully-Russ; Tobin Lopes (Adult Education Research Conference, 2018)
Using the PIAAC survey, this study examined social characteristics of work and cognitive skills. Results negatively associated collaboration at work and PIAAC scores, contradicting current thinking on workplace interactions.
Keywords: PIAAC; workplace collaboration; workforce development